2020
DOI: 10.21203/rs.3.rs-40285/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comorbidity Network Analysis of Depression, Anxiety and Stress During the COVID-19 Pandemic

Abstract: Background: Stress caused by the COVID-19 pandemic is highly correlated with depression and anxiety disorders, and there is currently a lack of understanding of the comorbidity network of these disorders. The purpose of this study is to explore the comorbidity network of depression, anxiety and stress during the COVID-19 pandemic through network analysis.Method: 887 participants are conducted a DASS 21 mental state survey across the country from February 18 to 22 in the outbreak of the COVID-19 pandemic in Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…For example, Bai et al (2021) also found "tense" a central symptom. Liang et al (2020) also identified "tense" or "I found it difficult to relax" in a Chinese population, although they used DASS-21 to assess symptoms. Nevertheless, while symptoms like "sadness", "unstoppable worry", and "irritability" were identified in other studies (e.g., Bai et al, 2021;Kaiser et al, 2020;Ren et al, 2021), our study did not.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bai et al (2021) also found "tense" a central symptom. Liang et al (2020) also identified "tense" or "I found it difficult to relax" in a Chinese population, although they used DASS-21 to assess symptoms. Nevertheless, while symptoms like "sadness", "unstoppable worry", and "irritability" were identified in other studies (e.g., Bai et al, 2021;Kaiser et al, 2020;Ren et al, 2021), our study did not.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the network analysis revealed nervousness and stress as bridge symptoms linking perceived stress with anxiety and depression disorders. 50 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the network analysis revealed nervousness and stress as bridge symptoms linking perceived stress with anxiety and depression disorders. 50 Depression, anxiety and stress are common MHD. Symptoms of one of these mental conditions increase the chances of getting other mental disorders, leading to diagnostic comorbidity.…”
Section: Discussionmentioning
confidence: 99%